Malignancy Rates in Thyroid Nodules Classified as Bethesda III and IV; Correlating Fine Needle Aspiration Cytology with Histopathology - Pereira, Chirag (Prague Medical Report, 2022)
Fine needle aspiration cytology (FNAC) is an integral part in the diagnostic work up of thyroid nodules. FNAC reports are based on Bethesda system for thyroid cytopathology which is one of the most commonly used systems worldwide. The main objective of the present study was to evaluate the malignancy rates in Bethesda category III and IV thyroid nodules over a six-year period. 642 thyroid FNAC were performed over a six-year period. The medical records of all these patients were reviewed using electronic patient records. Cases reported to have Bethesda category III and IV were included in the study. Data for these patients were reviewed to determine the relationship between these categories and thyroid cancer. There were 41 cases of category III of which 19 underwent surgery and the malignancy rates were found to be 26.3%. Category IV consisted of 50 cases of which 45 underwent surgery and the malignancy rates were 26.6%. The results from our study are similar to findings in larger multicentric studies which found that malignancy rates for Bethesda category III and IV were 10-30% and 25-40%, respectively.
Keywords: uzly štítné žlázy; Biopsy, Fine-Needle; lidé; Humans; tenkojehlová biopsie; Thyroid Nodule